What Happens in Winter? - Latta, Sara L. (Berkeley Heights, NJ : Enslow Publishers, 2006)
Simple text and full-color photographs introduce the characteristics of winter, and some of the things people and animals do during that time of year.
What are the seasons? -- When is it winter? -- Why is winter weather cold? -- What is winter like at the North and South Poles? -- What happens to plants in the winter? -- Where do animals go in the winter? -- What is hibernation? -- Winter fun -- A salty solution to icy streets.
Includes bibliographical references (p. 22) and index.
Keywords: Winter; Seasons